Persepsi Masyarakat terhadap Aktivitas Dakwah Salafi di Desa Suka Makmur Kecamatan Gunung Sahilan Kabupaten Kampar - Tata Anantia Syafitri; Tomi Hendra (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
Salafi is one of the streams of Islam that adheres to the strategies and patterns of da'wah carried out by the Prophet, companions, tabi'in and tabi'it tabi'in. Meanwhile, perception is the view or judgment of a person or group regarding a matter or object. This research was conducted in order to find out how the people in Suka Makmur Village perceive the da'wah activities held by the Salafi-based community and what activities are carried out by the Salafi-based community. This study uses a qualitative method. Data collection is done by observation, interviews and documentation. Based on the results of the research, the perception of the prosperous village community towards Salafi, which has developed since 2010, has no longer any resistance, such as when Salafi first entered the village, but there are still some people who still do not accept Salafi teachings, which are different from the teachings accepted by the community. The majority of people have accepted these differences in teachings as long as they do not deviate from the teachings of Islam.